Modelling value-added tax (VAT) in South Africa: Assessing the distributional impact of the recent increase in the VAT rate and options for redress through the benefits system - Rebone Gcabo; Boitumelo Moche; Wynnona Steyn; Boikhutso Moahlodi; Jukka Pirttilä; Michael Noble; Gemma Clare Wright; Helen Barnes; Faith Masekesa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Using SAMOD, a tax-benefit microsimulation model for South Africa, this paper examines the joint distributional impact of the increase in the value-added tax (VAT) rate and increases in benefit amounts in 2018. Although poverty and inequality did not increase overall, the poorest still saw a reduction in their purchasing power, as many of those in the lowest decile do not receive any social benefits. The paper then explores the consequences of eliminating zero-rating in VAT and using the generated revenues to finance new social benefits. The results suggest that a policy package of a uniform VAT and an expanded set of social benefits would lead to reduced poverty and inequality in comparison to the current practice of zero rating of some consumption goods in the VAT. The findings demonstrate the superiority of using direct taxes and benefits as opposed to provisions in indirect taxes in achieving redistribution.
Keywords: H23; H53; 330; value-added tax; microsimulation; redistribution; poverty; South Africa